CDR 2020
DOI: 10.20517/cdr.2020.71
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and redox signaling in CRPC progression: therapeutic potential of clinically-tested Nrf2-activators

Abstract: Androgen deprivation therapy (ADT) is the mainstay regimen in patients with androgen-dependent prostate cancer (PCa). However, the selection of androgen-independent cancer cells leads to castrate resistant prostate cancer (CRPC). The aggressive phenotype of CRPC cells underscores the need to elucidate mechanisms and therapeutic strategies to suppress CRPC outgrowth. Despite ADT, the activation of androgen receptor (AR) transcription factor continues via crosstalk with parallel signaling pathways. Understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 295 publications
(371 reference statements)
0
9
0
Order By: Relevance
“…However, increasing evidence suggests that ADT can induce oxidative stress by increasing ROS levels or decreasing cellular antioxidant system activity in surviving PC cells, which in turn cause genetic and epigenetic effects in PC. [29][30][31] Increased oxidative stress also causes redox signalling amplification and increases androgen receptor (AR) activation through several mechanisms, including AR overexpression, AR activation by co-regulators, mutation of AR and AR-related proteins, expression of AR splice variants, de novo androgen synthesis, etc. These alterations have pro-survival and anti-apoptotic effects on PC cells, resulting in the development of mCRPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing evidence suggests that ADT can induce oxidative stress by increasing ROS levels or decreasing cellular antioxidant system activity in surviving PC cells, which in turn cause genetic and epigenetic effects in PC. [29][30][31] Increased oxidative stress also causes redox signalling amplification and increases androgen receptor (AR) activation through several mechanisms, including AR overexpression, AR activation by co-regulators, mutation of AR and AR-related proteins, expression of AR splice variants, de novo androgen synthesis, etc. These alterations have pro-survival and anti-apoptotic effects on PC cells, resulting in the development of mCRPC.…”
Section: Discussionmentioning
confidence: 99%
“…The basic one, androgen deprivation therapy (ADT), is the first line of treatment against advanced PC and is also used as an adjuvant to local treatment in patients with high‐risk diseases. However, increasing evidence suggests that ADT can induce oxidative stress by increasing ROS levels or decreasing cellular antioxidant system activity in surviving PC cells, which in turn cause genetic and epigenetic effects in PC 29–31 . Increased oxidative stress also causes redox signalling amplification and increases androgen receptor (AR) activation through several mechanisms, including AR overexpression, AR activation by co‐regulators, mutation of AR and AR‐related proteins, expression of AR splice variants, de novo androgen synthesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, in DU145 NKO cells, no alteration was found in ROS content compared to control cells (Figure 5B). The complexity of redox‐regulated pathways in which a network of antioxidant proteins and transcription factors work together to maintain the ideal oxidative environment 23 could have compensated for the loss of NRF2 in DU145 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some data showed that the anti-cancer activity of phytochemicals involves the influence on many signaling pathways which control cell homeostasis. Interactions among Nrf2, NF-κB, and STAT3 signaling pathways, and their dysregulation, may play a key role in the development of cancer—including pancreatic cancer [ 22 , 43 , 44 , 45 ]—driven by the inflammation process. Signaling pathway NF-κB plays a crucial role in inflammatory response and production of pro-inflammatory molecules, including cytokines and enzymes such as COX-2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%